An Empirical Analysis of DDoS Attack Detection and Mitigation Techniques: A Comparative Review of Tools and Methods - Dr. Abhinandan Singh Dandotiya,; Palash Sharma,; Bharti gole,; Shruti Dubey,; Dr. Nidhi Dandotiya, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The availability and integrity of online services and networks are seriously threatened by distributed denial of service (DDoS) assaults. As a result, a plethora of detection and mitigation strategies have been created, all utilizing different instruments and approaches. By comparing various tools and approaches, this study provides an empirical examination of DDoS attack detection and mitigation strategies. We carefully assess the performance of top DDoS detection and mitigation solutions against a range of attack vectors and in diverse network contexts, taking into account their efficacy, efficiency, and accuracy. We examine the benefits, drawbacks, and real-world applications of both open-source and proprietary technologies for network defenders. Additionally, we look at how these tools and techniques adapt to changing threats and talk about new trends and difficulties in the DDoS assault arena. For network security practitioners, researchers, and policymakers looking for an understanding of the state of DDoS defence mechanisms and tactics for strengthening resilience against these disruptive cyber threats, this comparative assessment is an invaluable resource.
Keywords: DDoS Attack; Network Security; Detection Strategies; Mitigation Techniques; Cyber Resilience; Comparative Analysis